A decade of irrigation transforms the soil microbiome of a semi‐arid pine forest. Issue 4 (21st January 2017) - Hartmann, Martin; Brunner, Ivano; Hagedorn, Frank; Bardgett, Richard D.; Stierli, Beat; Herzog, Claude; Chen, Xiamei; Zingg, Andreas; Graf‐Pannatier, Elisabeth; Rigling, Andreas; Frey, Beat
Abstract: The impact of climate change on the soil microbiome potentially alters the biogeochemical cycle of terrestrial ecosystems. In semi‐arid environments, water availability is a major constraint on biogeochemical cycles due to the combination of high summer temperatures and low rainfall. Here, we explored how 10 years of irrigation of a water‐limited pine forest in the central European Alps altered the soil microbiome and associated ecosystem functioning. A decade of irrigation stimulated tree growth, resulting in higher crown cover, larger yearly increments of tree biomass, increased litter fall and greater root biomass. Greater amounts of plant‐derived inputs associated with increased primary production in the irrigated forest stands stimulated soil microbial activity coupled with pronounced shifts in the microbiome from largely oligotrophic to more copiotrophic lifestyles. Microbial groups benefitting from increased resource availabilities (litter, rhizodeposits) thrived under irrigation, leading to enhanced soil organic matter mineralization and carbon respired from irrigated soils. This unique long‐term study provides new insights into the impact of precipitation changes on the soil microbiome and associated ecosystem functioning in a water‐limited pine forest ecosystem and improves our understanding of the persistency of long‐term soil carbon stocks in a changing climate.